National evidence on glucose-lowering medication use for diabetes from 62 low- and middle-income countries - Teufel, Felix; Roddewig, Pia; Marcus, Maja E.; Theilmann, Michaela; Andall-Brereton, Glennis; Aryal, Krishna; Azadnajafabad, Sina; Bovet, Pascal; Dorobantu, Maria; Farzadfar, Farshad; Houehanou, Corine; Sibai, Abla; et al. (Nature Communications, 2025)
Given rising diabetes prevalence globally, access to diabetes treatments is gaining urgency. Yet, it remains unknown which glucose-lowering medication types people with diabetes across low- and middle-income countries (LMICs) use. In this cross-sectional analysis, we pooled nationally representative data of 223,283 adults aged ≥25 years in 62 LMICs from 2009 to 2019. We found that 51.9% [95%-CI: 49.6%, 54.2%] of 21,715 individuals with diabetes were undiagnosed. Among individuals with diagnosed diabetes, 18.6% [95%-CI: 14.5%, 23.4%] reported using no glucose-lowering medication, 57.3% [95%-CI: 53.1%, 61.4%] only used oral medication, 19.5% [95%-CI: 17.6%, 21.5%] used oral medication and insulin, and 4.7% [95%-CI: 3.9%, 5.6%] used insulin alone. In low-income countries, fewer individuals with diabetes were diagnosed and treated than in middle-income countries. Yet, among individuals who did get diagnosed, insulin use was two-thirds higher in low-income countries (38.9% [95%-CI: 31.6%, 46.7%]) compared to middle-income countries (23.2%; 95%-CI: 21.0%, 25.5%]). This finding could suggest a need for earlier diagnosis and treatment initiation. Our results can inform national and regional drug procurement efforts across LMICs.